Scleroderma-like Impairment in the Network of Telocytes/CD34+ Stromal Cells in the Experimental Mouse Model of Bleomycin-Induced Dermal Fibrosis - Irene Rosa (MDPI AG, 2021)
Considerable evidence accumulated over the past decade supports that telocytes (TCs)/CD34+ stromal cells represent an exclusive type of interstitial cells identifiable by transmission electron microscopy (TEM) or immunohistochemistry in various organs of the human body, including the skin. By means of their characteristic cellular extensions (telopodes), dermal TCs are arranged in networks intermingled with a multitude of neighboring cells and, hence, they are thought to contribute to skin homeostasis through both intercellular contacts and releasing extracellular vesicles. In this context, fibrotic skin lesions from patients with systemic sclerosis (SSc, scleroderma) appear to be characterized by a disruption of the dermal network of TCs, which has been ascribed to either cell degenerative processes or possible transformation into profibrotic myofibroblasts. In the present study, we utilized the well-established mouse model of bleomycin-induced scleroderma to gain further insights into the TC alterations found in cutaneous fibrosis. CD34 immunofluorescence revealed a severe impairment in the dermal network of TCs/CD34+ stromal cells in bleomycin-treated mice. CD31/CD34 double immunofluorescence confirmed that CD31−/CD34+ TC counts were greatly reduced in the skin of bleomycin-treated mice compared with control mice. Ultrastructural signs of TC injury were detected in the skin of bleomycin-treated mice by TEM. The analyses of skin samples from mice treated with bleomycin for different times by either TEM or double immunostaining and immunoblotting for the CD34/α-SMA antigens collectively suggested that, although a few TCs may transition to α-SMA+ myofibroblasts in the early disease stage, most of these cells rather undergo degeneration, and then are lost. Taken together, our data demonstrate that TC changes in the skin of bleomycin-treated mice mimic very closely those observed in human SSc skin, which makes this experimental model a suitable tool to (i) unravel the pathological mechanisms underlying TC damage and (ii) clarify the possible contribution of the TC loss to the development/progression of dermal fibrosis. In perspective, these findings may have important implications in the field of skin regenerative medicine.